Crecimiento vía exportaciones: el caso Colombia - Corea del Sur (2009)
Relations between Colombia and South Korea have been marked by political and economic cooperation between both countries. In economic cooperation, the relationship has been a leader-follower type in Korea as a developed country that has supported Colombia through technical cooperation aimed at the development of the country, and Colombia as a follower has been the executioner of those resources. However, it is possible to achieve beneficial cooperation for both countries through a detailed analysis of bilateral trade. This paper proposes a methodology to identify strategies for trade cooperation between the two countries.The results suggest that Colombia should direct their changing production towards products with high strategic value on Korea currently has comparative advantage.